2002
DOI: 10.1034/j.1600-0420.2002.800211.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorzolamide and ocular blood flow in previously untreated glaucoma patients: a controlled double‐masked study

Abstract: ABSTRACT.Purpose: The aim of this study was to investigate the haemodynamic effects of topical dorzolamide treatment in eyes with newly detected and previously untreated glaucoma. Methods: Forty-seven patients with open angle glaucoma were consecutively randomized to dorzolamide versus placebo TID during a 6-week double-masked treatment trial. Ocular blood flow was investigated at baseline and on therapy using colour Doppler imaging of the retrobulbar vessels and scanning laser ophthalmoscope fluorescein angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 27 publications
0
29
3
2
Order By: Relevance
“…This confirms previous studies that underlined that normal-tension glaucoma and chronic, open-angle glaucoma are characteristically associated with reduced flow velocities and increased ophthalmic artery resistance indexes. [31][32][33][34][35][36] Although it has been reported that aging, increased plasma viscosity, and atherosclerosis render the monkey retina susceptible to ischemia, 37 in the present study no differences in age and plasma viscosity 7 values were observed either in normal, healthy women or in those who presented with ocular disease. Thus, other factors may intervene in reducing retrobulbar perfusion both in normal-tension and open-angle glaucoma.…”
Section: Battaglia Et Alcontrasting
confidence: 83%
“…This confirms previous studies that underlined that normal-tension glaucoma and chronic, open-angle glaucoma are characteristically associated with reduced flow velocities and increased ophthalmic artery resistance indexes. [31][32][33][34][35][36] Although it has been reported that aging, increased plasma viscosity, and atherosclerosis render the monkey retina susceptible to ischemia, 37 in the present study no differences in age and plasma viscosity 7 values were observed either in normal, healthy women or in those who presented with ocular disease. Thus, other factors may intervene in reducing retrobulbar perfusion both in normal-tension and open-angle glaucoma.…”
Section: Battaglia Et Alcontrasting
confidence: 83%
“…However, the results of our study are in contradiction to the fi ndings reported by Bergstrand and colleagues 23 in previously untreated glaucoma patients. These authors did not fi nd dorzolamide to exert signifi cant hemodynamic effects.…”
Section: Discussioncontrasting
confidence: 57%
“…The end-diastolic velocities and RI, in all retrobulbar vessels, reported by Bergstrand and colleagues 23 seemed to be signifi cantly lower than those reported by our group. These differences in the retrobulbar hemodynamics between the two study patients may be clinically relevant.…”
Section: Discussioncontrasting
confidence: 55%
“…[28][29][30] However, Latina and colleagues 31 found that dorzolamide-not brimonidine-caused a statistically significant and sustained improvement in blood flow from baseline in the superotemporal and nasal peripapillary retinal regions using SLDF as examining tool. Scanning laser Doppler flowmeter is a noninvasive method, which allows blood flow measurement in specific retinal areas.…”
Section: Simsek Et Al 82mentioning
confidence: 93%